The Relation Between Serum P-selectin, Thrombin-activatable Fibrinolysis Inhibitor Levels, and Carotid Artery Intima-media Thickness in Acute Ischemic Stroke - Dilek Yılmaz (Türk Nöroloji Dergisi, 2020)
Objective: Inflammation and migration of leukocytes to the brain parenchyma play a role in atherosclerosis and cerebral ischemic stroke. Migration occurs with the help of adhesion molecules on the surface of cerebral endothelial cells and leukocytes. P-selectin, an adhesion molecule, is present on the platelet and endothelial surface and allows leukocytes to loosely adhere to the endothelium, and its increase has been shown in acute ischemic stroke (AIS). Thrombin-activatable fibrinolysis inhibitor (TAFI) is a procarboxypeptidase molecule that can be another marker of AIS, which has been shown to increase the risk of thromboembolism and stroke 6-fold. Intima-media thickness (IMT) is thought to be associated with atherosclerotic diseases in carotid ultrasonography (USG) and increased risk of ischemic stroke has been found to be associated with increased carotid IMT. In this study, we investigated the relationship between P-selectin and TAFI levels, which have been shown to be effective for AIS via carotid IMT, and is considered significant for atherosclerosis. Materials and Methods: Forty patients with AIS and 22 healthy subjects were included in the study. In both groups, serum P-selectin and TAFI levels were studied at the time of presentation, and on day 7, day 14, and at one month; carotid IMT and stenosis rates were measured by Doppler USG. P-selectin and TAFI levels were compared with carotid IMT in both groups. Results: There was no significant difference between P-selectin levels and carotid IMT between the groups; TAFI levels were significantly higher in the patient group and were correlated with carotid IMT in both groups. Conclusion: TAFI increase has been suggested to be a marker of early atherosclerosis in asymptomatic atherosclerosis and ischemic stroke. A positive correlation between TAFI levels and carotid IMT and stenosis rates have been reported; however, the positive correlation between increased P-selectin levels in AIS and carotid IMT was not detected in our study.